The Impact of Digital Ecosystems on the Financial Management Efficiency in State Institutions - YATSUKH, Olena; CHYHYRYNSKYI, Artem; PURHANI, Safar Hasan; BULHAKOVA, Olena; DURMAN, Mykola (Theoretical and Practical Research in Economic Fields; Vol 15 No 2 (2024): TPREF, Volume XV, Issue 2(30), Summer 2024, Special Issue, 2024)
Purpose: Digital ecosystems are a key driver of development at the current stage, in particular, in state institutions. Increasing efficiency of financial management through digitalization in the public sector is one of the key directions. The aim of the study is to determine the impact of digital ecosystems on the results of financial management in Ukrainian and Azerbaijani public institutions. Methodology: The research employed the methodological tools of regression and correlation analysis, as well as descriptive statistics to determine the impact of digitalization on the effectiveness of financial management of institutions. The application of the least squares method revealed a statistically significant positive effect of digital technology spending (β1 = 0.0528, p = 0.010) on management efficiency, while other variables showed insignificant or negative effects. The model explains 43.6% of the variation in the dependent variable, with R-squared = 0.436 and Adjusted R-squared = 0.285. Findings: Correlation analysis confirmed a strong positive relationship (r=0.58) between digitization costs and management efficiency. The article provides practical recommendations for optimizing the implementation of digital technologies in the management of public finances, including the development of electronic services and increasing the level of digital literacy. Originality: Further research in the chosen direction will be focused on the formation and implementation of a system of key indicators of the effectiveness of digital ecosystems from the perspective of the efficiency of financial management in public institutions of Ukraine and Azerbaijan.